The Welfare Effects of Peer Entry: The Case of Airbnb and the Accommodation Industry - Farronato, Chiara; Fradkin, Andrey (American Economic Review, 2022)
We study the welfare effects of enabling peer supply through Airbnb in the accommodation industry. We present a model of competition between flexible and dedicated sellers (peer hosts and hotels) who provide differentiated products. We estimate this model using data from major US cities and quantify the welfare effects of Airbnb on travelers, hosts, and hotels. The welfare gains are concentrated in specific locations (New York) and times (New Year’s Eve) when hotel capacity is constrained. This occurs because peer hosts are responsive to market conditions, expand supply as hotels fill up, and keep hotel prices down as a result. (JEL L11, L83, L86, L88, Z31)